On the Relationship between Reflective Teaching and Personality Traits - Seyed Mojtaba Marashi (Journal of English Teaching, 2023)
Abstract: During the last decade, the slogan of reflective teaching has been embraced by teachers, teachers’ educators, and educational teachers all over the world. This international movement in teaching and teacher education that has developed under the banner of reflection can be seen as a reaction against the view of teachers as technicians who narrowly construe the nature of the problems confronting them and merely carry out what others, removed from classroom, want them to do. Drawing on John Dewey’s ideas, there are three attitudes of reflective teachers, i.e., open-mindedness, wholeheartedness, and responsibility. Personality traits are tendencies that represent an individual's uniqueness that have a lasting and stable effect on an individual's behavior and thinking (Satchell et al., 2017). However, given the fact that all teachers are not of the same personality types, it is hypothesized that teachers with one personality type prefer to rely on one element of teaching reflection. This provided enough impetus for us to investigate the relationship between the teachers’ personality types and their teaching reflection elements. To this end, we drew on John and Srivastava’s (1999) the Big Five Inventory Personality Test and Ryan (2014) the Reflective Teaching Instrument. One hundred Iranian EFL teachers were selected based on convenience sampling. They were from six different language institutes in Tehran, Iran. The results confirmed the hypothesis that each personality type correlated with elements of the teaching reflection. Extrovert teachers, for instance, were found to draw on the affective element in their teaching practices. The pedagogical implications of the findings are discussed.